2022
DOI: 10.4103/ijo.ijo_1652_21
|View full text |Cite
|
Sign up to set email alerts
|

Orbital magnetic resonance imaging profile and clinicoradiological correlation in COVID-19-associated rhino-orbital-cerebral mucormycosis: A single-center study of 270 patients from North India

Abstract: Purpose: To study the clinical profile and magnetic resonance imaging (MRI) features in patients of COVID-19-associated rhino-orbital-cerebral mucormycosis (CA-ROCM) with orbital involvement and perform a clinicoradiological correlation. Methods: A cross-sectional study was performed at a tertiary care center in north India from May 2021 to June 2021. Consecutive patients with clinical, nasal endoscopic, and/or microbiological evidence of CA-ROCM underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
2
6
0
1
Order By: Relevance
“…In concurrence with our study, the most common presenting symptoms reported by a cross-sectional study on 270 CA-ROCM patients and a prospective study on 49 CA-ROCM patients were facial/periorbital pain and swelling 19,22 . A systematic review and meta-analysis on 2,312 proven CAM patients reported headache (54%), periorbital swelling/pain (53%), facial swelling/pain (43%), ophthalmoplegia (42%), proptosis (41%), and nasal discharge/congestion (36%), decreased or loss of vision (31%), ptosis (28%), dental pain or loosened teeth (25%), palatal discoloration or ulcers (22%) as common symptoms 13 , which are almost consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In concurrence with our study, the most common presenting symptoms reported by a cross-sectional study on 270 CA-ROCM patients and a prospective study on 49 CA-ROCM patients were facial/periorbital pain and swelling 19,22 . A systematic review and meta-analysis on 2,312 proven CAM patients reported headache (54%), periorbital swelling/pain (53%), facial swelling/pain (43%), ophthalmoplegia (42%), proptosis (41%), and nasal discharge/congestion (36%), decreased or loss of vision (31%), ptosis (28%), dental pain or loosened teeth (25%), palatal discoloration or ulcers (22%) as common symptoms 13 , which are almost consistent with our study.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other studies 20,22 , ptosis, periorbital edema, periocular pain/tenderness, ophthalmoplegia, and proptosis are common ocular and periocular signs and symptoms among CA-ROCM patients. Of 35 involved eyes in a cross-sectional study, retinal artery occlusion and disc edema were observed in 23% and 11%, respectively 20 .…”
Section: Discussionsupporting
confidence: 91%
“…Apart from the commonly mentioned rhino-orbital-cerebral mucormycosis [ 16 ], COVID-19-related orbital abscess has been sporadically reported in the literature [ 17 ]. Indeed, approximately 1–6% of OWF (especially those with sinusitis 1–2 weeks pre-trauma or as long as 4–5 weeks post-injury [ 14 , 15 ]) develop orbital cellulitis, and 4% of which extend intracranially, e.g., in the form of cavernous sinus thrombosis, meningitis, or subdural or cerebral empyema [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. In our study, there was no orbital cellulitis because patients with underlying rhinosinusitis and/or eye diseases were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was no orbital cellulitis because patients with underlying rhinosinusitis and/or eye diseases were excluded. However, anaerobic cellulitis resulting from orbital tissue hypoperfusion due to the fracture [ 16 ], or a COVID-prothrombotic event [ 1 , 15 , 17 ] may be developed in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is well known to result in pulmonary and multiple extra-pulmonary manifestations [ 1 ]. Among the extra-pulmonary manifestations, head and neck involvement, primarily of the sino-nasal, orbital and otic compartments, were increasingly recognized during the second wave of pandemic [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%